Law Enforcement Against Fraudulent Acts Committed in Cyberspace - Dianto Gunawan Tamba; Indah Sya Vitri; Felix Adrian Sembiring; Yolanda Anatasya Sembiring (SEAN Institute, 2026)
These developments have created new business opportunities that enable individuals to conduct legal transactions involving online sales/e-commerce. However, these developments also have negative aspects/problems that are detrimental to consumers, namely criminal acts of fraud committed by irresponsible parties, particularly sellers, as well as inadequate law enforcement, including problems with evidence. This needs to be discussed because of the problem of evidence, namely electronic data that is easy to falsify, the lack of readiness of law enforcement, and in order to reduce online fraud. The author's suggestion is that there should be stricter law enforcement and evidence from law enforcement officials, and the community should also play a role in reducing the use of the internet that is harmful to society. Cultural factors within a community are also important.